Implementation of the Pancasila Student Profile in Pancasila Education Subjects to Improve Democratic Character - Octavia , Azka Azizah; Tirtoni, Feri (Lectura : Jurnal Pendidikan, 2024)
The Pancasila learner profile is an implementation of the Merdeka curriculum which includes the character building of students. Character education is closely related to the Pancasila learner profile in the Merdeka curriculum in a formal education environment which aims to shape character in accordance with the values of Pancasila. Pancasila education is one of the subjects integrated with the Pancasila learner profile. Meanwhile, the character of democracy in research can develop through the Pancasila learner profile applied in the classroom. So, the purpose of this study is to describe the form of implementation of the Pancasila learner profile in Pancasila education subjects to improve the democratic character of 4th grade elementary school students and to determine the impact of the implementation of the Pancasila learner profile on democratic character. This research is a qualitative research. This research data comes from observation results, interview results, and results, documentation. Data analysis used in the form of data reduction, data display, and conclusing drawing. The results showed that the implementation of the Pancasila learner profile at SDN Barengkrajan 2 in the Pancasila Education subject found no obstacles, it's just that teachers still need adjustments in its implementation. The Pancasila learner profile has a good impact on the development of students' democratic character because the implementation of the Merdeka curriculum emphasizes students so that students can be free in shaping democratic character in learning activities.